The effect of financial factors on tax avoidance in mining companies listed on the indonesia stock exchange 2018 – 2020 (Asian Journal of Economics and Business Management, 2022)
Taxes have a significant role in the development and support of the running of a country's government. Tax collection is used to finance all expenditures issued by the state in order to realize national development. Tax payments are also a manifestation of the state's obligations and the participation of the community in collecting funds to finance the state in national development. This study aimed to determine the effect of profitability and company size on tax avoidance in 2018-2020. In this study, the research method used is descriptive analysis and quantitative techniques, collecting secondary data from the 2018-2020 financial statements. The sampling method used in this research is using a purposive sampling method. The sample set in this study is 30 mining companies listed on the Indonesia Stock Exchange that meet the criteria. The normality test, namely the Kolmogorov-Smirnov test, was used in this study to test whether the data were normally distributed or not. When the data were not normally distributed, it is done by case wise diagnostic. The results showed that the profitability and firm size has a test that is less than 0.05, it can be concluded that profitability and firm size did not affect tax avoidance.